Analisis Kinerja Pelayanan Fasilitas Penumpang Stasiun Kereta Api Manggarai Berdaarkan Standar Pelayanan Minimum dan Importance Performance Analysis (IPA) - Deary Tree Nowi Putri Galuh; Siti Sahara (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
The main objective of this research is to determine whether the service performance of Manggarai Station meets the minimum service criteria and determine the significance of service performance for station visitors using Importance Performance Analysis (IPA). The data for this research came from surveys, direct observation, and a review of related literature. The researcher then used quantitative methodology with descriptive analysis techniques to conclude the results. 50 people filled out questionnaires over two days. According to the results, every station under construction meets minimum service standards, including having accessible toilets for people with disabilities. Manggarai Station users give high marks to the facilities and services provided by the station. Customers think that well-maintained facilities and services can greatly enhance a brand's travel experience. Therefore, to make Manggarai Station more friendly and aesthetic for new arrivals, services and facilities must be improved regularly.